Ethical AI Learning and Social Skill Enhancement in Higher Education: A Systematic Review - Soraya, Zazak (Proceeding International Conference on Religion, Science and Education, 2024)
Artificial Intelligence (AI) is progressively shaping the educational landscape, offering new opportunities to enhance teaching and learning. This review aims to investigate the ethical dimensions of AI and its impact on social skills in higher education. It employs a systematic review of peer-reviewed literature to explore the ethical considerations surrounding AI integration in educational settings. The research delves into the ethical aspects of AI’s role in fostering students’ social skills and provides recommendations for future research. Ethical AI learning principles encompass openness, fairness, privacy, accountability, and inclusivity. Additionally, this study emphasizes the importance of nurturing students’ social abilities and highlights how effective leadership and collaborative techniques can improve social connections among academic staff.